Theoretical substantiation of regular system of horizontal drains (a new approach) - Poliakov, V.L. (Доповіді НАН України, 2023)
The nonlinear problem of regulating the water-physical conditions of over-drained and over-wetted agricultural lands through a regular system of horizontal drains has been formulated and solved by analytical methods. The dynamics of groundwater reserves are analyzed in a generalized manner, rather than locally as done previously. A dependence has been derived to describe the behavior of the water table averaged over the interdrain space, considering a targeted change in head within the drains. Based on this, a formula has been obtained for calculating the optimal drain spacing in both homogeneous and heterogeneous soils, taking into account the requirements for their water-physical state. An assessment was conducted on the uneven distribution of groundwater caused by the local action of horizontal drains. Examples with typical initial data illustrate the decrease in the average water table over time and demonstrate the potential for rarefaction of reclamation drainage using a new methodological approach. This approach will significantly reduce capital costs for its construction and reconstruction.